Pengaruh Halal Awarness, Sertifikasi Halal dan bahan makanan Halal terhadap keputusan pembelian produk makanan di Era Pandemic Covid-19 - Asqalani Rifai, Muhammad Syakib; Nurhidayat, Wildan; Prianka, Winda Gafrilia; Salsabila, Fahma Labiba; Nabilah, Syifa Syaliya (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
The city of Bandung as a leading tourist destination and supported by the image of Bandung City as a culinary center in West Java is the main focus. Currently, it can be seen that the impact of the Covid-19 pandemic has decreased in terms of sales in the food and beverage industry. During the Covid-19 pandemic, there were still food products that did not have halal certificates on a national scale, apparently it did not discourage consumers, especially those who were Muslim, from buying these products/types of food. This study aims to determine the extent to which halal certificates, halal awareness and food composition affect consumer buying interest. This research was conducted using a quantitative descriptive method involving 300 respondents. The results of the study show that the three variables of halal certificates, halal awareness and food composition have an influence on consumer buying interest.